PHYSICAL EVALUATION OF CURCUMA RHIZOME EXTRACT (Curcuma xanthorrhiza) FORMULATION IN ANTI ACNE LOOSE POWDER - Marini Marini; Haty Latifah Priatni; Azmi Darotulmutmainnah; Dea Safitri (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
When Staphylococcus aureus and Staphylococcus epidermis are isolated from acne-proneskin, the essential oil and curcuminoids in curcumin (Curcuma zanthorrhiza Roxb) exhibitantibacterial activity against blemished skin. The purpose of this study was to create an antiacne loose powder using Curcuma rhizome extract and to determine which formulationsmeet the best test requirements. Extraction was carried out using the maceration methodwith 96% ethanol solvent. The powder formulation consisted of alba bolus, magnesiumcarbonate, magnesium stearate, zinc oxide, oleum rosae, and talc, developed withtemulawak rhizome extract at concentrations of F0 (0%), F1 (8%), F2 (10%), and F3 (12%).The evaluation of the powder preparation was organoleptic, humidity, powder flow rate,specific gravity, and pH.. The results indicated that the F1 formulation's humidity test resultsof less than 10%, the speed of the powder flow evaluation test results was 15.6%, the angleof repose test result was 26.6°, and the measurement of pH showed that the result of 6fulfilled the requirements. Based on a physical test of the anti-acne loose powder, theCurcuma rhizome extract in the FI formulation with an 8% concentration produced optimalresults. Keywords: anti acne, physical evaluation, loose powder, curcuma